Foreign body aspiration in children - E., Sivakumar; P., Ramasubramaniam (International Journal of Contemporary Pediatrics, 2019)
Background: Foreign Body (FB) aspiration is a life-threatening problem in children. Here the demographic pattern, clinical presentation, type of Foreign Body (FB) and outcome of FB aspiration was examined. Methods: An observational case series study done in Institute of child health and research centre, Government Rajaji hospital, Madurai during November 2015 to June 2018. After a detailed history and clinical examination, children with definite evidence of FB in tracheobronchial tree were subjected to rigid bronchoscopy and with doubtful evidence were subject to FFBS. They were followed up for complications. Results: Of the 136 children, 86.03% (n=117) were under 3 years of age. A positive history of FB aspiration was present only in 51.4% (n=70). Unilateral hyperinflation was seen in 48.53% (n=66) but was normal in 13.97% (n=19). Flexible Fiber Optic Bronchoscopy (FFBS) diagnosed FBs in 61.02% (n=83) which included children with acute onset breathlessness and persistent radiological features. Peanut was the most common FB 64.71% (n=44). FBs were found in the right side in 50% (n=34) and in the left in 38.2% (n=26). 36% (n=49) developed complications due to the FBs and 2.9% (n=4) due to procedure. Conclusions: FB aspiration is most common in children less than 3 years of age. Positive history of aspiration was seen in only 51.4% and chest X-ray was normal in 13.97%. FFBS diagnosed FB in 61.02%. Peanut was the most common FB. Persistent pneumonitis is the most common complication.